Swedish registers to examine drug safety and clinical issues in RA. Issue 6 (13th January 2006) - Askling, J; Fored, C M; Geborek, P; Jacobsson, L T H; van Vollenhoven, R; Feltelius, N; Lindblad, S; Klareskog, L
Abstract : Data from several different monitoring systems are examined. The potential for registers based on data obtained from clinical practice, and linkage of such data to national health and population registers, is discussed. The approach described is a possible prototype for long term surveillance systems needed for the safe introduction of new treatments.